Formula Apportionment and Transfer Pricing under Oligopolistic Competition - Søren Bo Nielsen; Pascalis Raimondos-Møller; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper demonstrates that under conditions of imperfect (oligopolistic) competition, a transition from separate accounting (SA) to formula apportionment (FA) does not eliminate the problem of profit shifting via transfer pricing. In particular, if affiliates of a multinational firm face oligopolistic competition, it is beneficial for the multinational to manipulate transfer prices for tax-saving as well as strategic reasons under both FA and SA. The analysis shows that a switch from SA rules to FA rules may actually strengthen profit shifting activities by multinationals.
Keywords: 330